The impact of healthy behaviors and physical activity on preventing cognitive impairment among older residents in Taipei - Wan-Yu Lin; Yu-Kai Lin (Archives of Gerontology and Geriatrics Plus)
Background: With the rapid aging of the population, the prevalence of dementia among older adults has been increasing. This study aims to investigate the impact of healthy lifestyle behaviors and physical activity on the attenuation of cognitive decline in older adults. Methods: This study longitudinally analyzed health examination data from older adults aged 65 and above in Taipei between 2005 and 2010. A total of 30,314 participants provided self-reported data through structured questionnaires on their health-related behaviors (tobacco use, alcohol consumption, vegetables and fruits intake, and milk consumption), engagement in physical activity and cognitive function. The Cox proportional hazards model was employed for data analysis. Results: The findings indicated that older adults who occasionally consumed alcohol exhibited a 47 % (95 % CI: 0.42–0.68) lower risk of developing cognitive impairment. Individuals who did not consume vegetables and fruits daily had a 23 % (95 % CI: 1.06–1.43) higher risk of cognitive impairment compared to those with regular consumption. Furthermore, older adults who engaged in consistent physical activity demonstrated a reduced risk of cognitive impairment relative to their inactive counterparts. Specifically, individuals who exercised 1–2 times per week and those who were entirely sedentary exhibited an increased risk of 20 % (95 % CI: 1.04–1.38) and 84 % (95 % CI: 1.52–2.22), respectively. Conclusions: This study provides empirical evidence that adherence to healthy lifestyle behaviors significantly contributes to mitigating cognitive decline in older adults. Moreover, these behaviors are feasible and adaptable in later life.